2016
DOI: 10.1111/opec.12073
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of oil price, exchange rate and inflation on the economic activity of Malaysia

Abstract: The purpose of this study is to examine the short and long‐run impacts of crude oil price (CP), exchange rate (EXR) and inflation (CPI) on the economic activity (GDP) of Malaysia within the framework of the vector error correction model (VECM). The results suggest that CP positively affects GDP in the short‐run and the tests do not identify any significant impacts of EXR and CPI on the GDP. However, all these variables maintain a long‐run relationship with GDP. The causality tests have shown unidirectional Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This finding coincided with the results of a number of studies, including: (Jongwanich & Park, 2011) study on a number of Asian developing countries and (Basnet & Upadhyaya, 2015) study on ASEAN countries, in which the researchers pointed out that there is a limited impact of oil prices on inflation in these countries except for Thailand. (Mantai & Alom, 2016) study found that there is no statistically significant effect of oil prices on inflation rate in Malaysia. important in the G7 for several reasons, including:…”
Section: Introductionmentioning
confidence: 82%
“…This finding coincided with the results of a number of studies, including: (Jongwanich & Park, 2011) study on a number of Asian developing countries and (Basnet & Upadhyaya, 2015) study on ASEAN countries, in which the researchers pointed out that there is a limited impact of oil prices on inflation in these countries except for Thailand. (Mantai & Alom, 2016) study found that there is no statistically significant effect of oil prices on inflation rate in Malaysia. important in the G7 for several reasons, including:…”
Section: Introductionmentioning
confidence: 82%
“…The common problems occur in the oil exporting countries when oil prices decrease are mainly due to the strong dependence on oil and gas exports (Mantai and Alom, 2016). It is called the Dutch disease in which the country is experiencing a negative impact of large foreign income derived from abundance of the specific natural resource.…”
Section: Introductionmentioning
confidence: 99%